2021
DOI: 10.1590/1980-265x-tce-2020-0494
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated With Locomotive Syndrome in Community-Dwelling Older Adults

Abstract: Objective: to analyze prevalence and the factors associated with locomotive syndrome in community-dwelling older adults. Method: a cross-sectional study, developed in a municipal center for the care of older adults in Teresina, Piauí, Brazil. The sample was for convenience and comprised 204 older adults aged 60 years or more, of both genders and with preserved cognitive capacity, according to parameters of the Mini Mental State Examination. Data collection occurred from March to November 2018, by applying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Frailty is a multidimensional syndrome, defined as a clinical state of extreme vulnerability that contributes to homeostatic imbalance in the organism, decline of the physiological system, and cognitive, psychological and social changes. Its prevalence increases with age, and can result in greater disability and dependence in old age [6][7] . A mixed methods study conducted with 121 potentially frail community-dwelling older adults showed the importance of the support provided by the family, neighbors and friends as a strategy for coping with the condition of frailty 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Frailty is a multidimensional syndrome, defined as a clinical state of extreme vulnerability that contributes to homeostatic imbalance in the organism, decline of the physiological system, and cognitive, psychological and social changes. Its prevalence increases with age, and can result in greater disability and dependence in old age [6][7] . A mixed methods study conducted with 121 potentially frail community-dwelling older adults showed the importance of the support provided by the family, neighbors and friends as a strategy for coping with the condition of frailty 8 .…”
Section: Introductionmentioning
confidence: 99%
“…A fragilidade é uma síndrome multidimensional, definida como um estado clínico de extrema vulnerabilidade que contribui para o desequilíbrio homeostático do organismo, o declínio do sistema fisiológico, as alterações cognitivas, psicológicas e sociais. A prevalência desta aumenta com a idade, e pode resultar em quadro de maior incapacidade e dependência na velhice [6][7] . Estudo de métodos mistos com 121 idosos potencialmente frágeis da comunidade demonstrou a importância do apoio familiar, de vizinhos e amigos como estratégia de enfrentamento da condição de fragilidade 8 .…”
Section: /16 Introduçãounclassified
“…The Japanese Orthopedic Association (JOA) has proposed the concept of the locomotive syndrome (LS), which refers to 1) conditions that will require due care and consideration, or 2) high-risk conditions that need nursing long care soon because of locomotive organ dysfunction in the older people [3]. The prevalence of LS among seniors has been reported as 16% to 40% in various studies [4,5]. According to some studies, 44% to 60% of the Iranian older people have physical and locomotive disabilities [6,7].…”
Section: Introductionmentioning
confidence: 99%